P11.27 Drug screening of available anti-cancer drugs on patient-derived GBM cultures identifies candidate treatments for a subpopulation of GBM patients - Ntafoulis, I (Neuro Oncol, 2019)
BACKGROUND: The development of new therapeutic agents generally takes many years to translate to clinically-effective new treatments. Among the strategies to reduce this time frame, efforts are now being undertaken to investigate drug repurposing. With this approach, compounds available for a specific disease are evaluated for their therapeutic efficacy in other diseases. We have set up a patient-derived cell culture model to apply this strategy for glioblastoma (GBM). MATERIAL AND METHODS: Fresh patient-derived tumour tissue was dissociated and cultured in serum-free medium supplemented with EGF and bFGF. MGMT status was determined by methylation-specific PCR.Drug screening was performed using the NIH anti-cancer collection containing 114 approved oncology drugs. Compounds include chemotherapeutic agents as well as small molecule targeted agents. Readout for drug effects is based on ATP-based viability assay. Using systems modelling approaches, integrated analysis of both mutational and expression data of each tumour is applied to identify key pathways involved in response to specific compounds. RESULTS: Molecular analysis demonstrated that copy number variations are preserved under serum-free culture conditions and that the MGMT methylation status is retained in over 75% of cases. Screening of the NIH anti-cancer collection on 55 GBM cell cultures revealed high intertumoral variation in response to most drugs. This included subsets of GBM revealing exceptionally high sensitivity to specific agents at clinically-feasible concentrations. Further ranking of the compounds was made based on the therapeutic index (IC50 tumour versus normal human astrocytes) and predicted blood-brain-barrier crossing capability. Currently, integrated analysis of molecular profiles of the tumour in relation to the drug response data is ongoing with the aim of identifying response predictors to these clinically-approved anti-cancer agents. CONCLUSION: Our patient-derived in vitro drug screening assay may offer a tool to identify available anti-cancer agents that are effective in a subpopulation of GBM patients and that may be implemented in future stratified clinical trials for this patient group.